P2X7 receptor as a key player in pathological pain: insights into Neuropathic, inflammatory, and cancer pain - Jiang, Pan; Wang, Cai; Jia, Fajing; Wu, Hua; Hao, Haihu; Jing, Shaoze (Frontiers in Pharmacology, 2025)
Purinergic P2X7 receptor (P2X7R) is a widely distributed, non-selective ATP-gated ion channel that plays a crucial role in the regulation of neuropathic pain, inflammatory pain, and cancer pain. Understanding the function and mechanisms of P2X7R in these various pain conditions, as well as utilizing P2X7R-targeted treatments, may offer a promising strategy for alleviating or resolving pathological pain. As a result, P2X7R and its antagonists have been the subject of extensive research, leading to the development of several P2X7R antagonists that have shown promising antinociceptive effects in numerous preclinical studies. However, further investigation and development are still necessary to fully realize their therapeutic potential. This review will provide an overview of the structure and function of P2X7R, its role in different pathological pain conditions, and the latest advances in the development of P2X7R antagonists, with the goal of offering new insights into the treatment of pathological pain.